The Global Political Economy of Trade Protectionism and Liberalisation. (Taylor & Francis, 2012)
Given the widely-accepted premise that free trade is the best means of maximising overall societal welfare, why has it proven so difficult to achieve in certain industries? This book tackles arguably the most perennial and deep-rooted of all questions in political economy, and questions the incumbent orthodox liberal theories of collective action.Using a historical institutionalist framework to explore and explain the political economy of trade protectionism and liberalization, this book is based on detailed case studies of the textiles and clothing sector in the EU, United St.